Analisis Faktor Penyebab Kepailitan dan Dampak Penutupan PT Sritex - Laura Aulia Rosaline (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2025)
This research aims to find out the factors that caused the bankruptcy of PT Sritex and to find out the impact caused by the closure of PT Sritex as of March 2025. The research method used in this research is the normative method with reference to Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations. The results showed that there were several factors that caused the bankruptcy of PT Sritex, namely unmanageable debt, the failure of the peace agreement, and the covid-19 pandemic which caused losses to PT Sritex. After being declared bankrupt by the Semarang Commercial Court, the creditors' meeting in bankruptcy agreed that there was no going concern for PT Sri Rejeki Isman (Sritex), so that the next process continued to debt settlement. Therefore, the impact caused by the closure of PT Sritex, namely the impact on PT Sritex employees, the textile industry, and PT Sritex creditors.